Timed artificial insemination in beef cattle using GnRH agonist, PGF2alpha and estradiol benzoate (EB) - Fernandes, P.; Teixeira, A. B.; Crocci, A. J.; Barros, C. M. (Elsevier B.V., 2001)
The present work evaluated low-cost protocols for timed artificial insemination (TAI) in beef cattle. In Experiment 1, cycling nonlactating Nelore cows (Bos indicus, n=98) were assigned to the following groups: GnRH-PGF (GP) and GnRH-PGF-GnRH (GPG), whereas cycling (n=328, Experiment 2) or anestrus (n = 225, Experiment 3) lactating (L) cows were divided into 3 groups: GP-L, GPG-L and GnRH-PCF-Estradiol benzoate (GPE-L). In Experiment 4, lactating cows (n=201) were separated into 3 groups: GP-L, GPE-L and G 1/2PE-L. Animals from Experiment 1, 3 and 4 were treated (Day 0), at random stages of the estrous cycle, with 8 mug of buserelin acetate (GnRH agonist) intramuscularly (im), whereas in Experiment 2 half of the cows received 8 and the other half 12 mug of GnRH (im). Seven days later (D 7) all animals were treated with 25 mg of dinoprost trometamine (PGF2 alpha, im) except those cows from the G 1/2PE-L group which received only 1/2 dose of PGF2 alpha (12.5 mg) via intravulvo-submucosa (ivsm). Alter PGF2 alpha injection the animals from the control groups (GP and GP-L) were observed twice daily to detect estrus and Al was performed 12 h afterwards. The cows from the other groups received a second GnRH injection (D 8 in GPG-L and d9 in GPG groups) or one injection of estradiol benzoate (EB, 1.0 mg, D 8 in GPE-L group). All cows from GPG and GPG-L or GPE-L groups were AI 20 to 24 or 30 to 34 h, respectively, after the last hormonal injection. Pregnancy was determined by ultrasonography or rectal palpation 30 to 50 days after AI. In the control groups (GP and GP-L) percentage of animals detected in heat (44.5 to 70.3%) and pregnancy rate (20 to 42%) varied according to the number of animals with corpus luteum (CL) at the beginning of treatment. The administration of a second dose of GnRH either 24 (Experiment 2) or 48 h (Experiment 1) after PGF2 alpha resulted in 47.7 and 44.9% pregnancy rates, respectively, after TAI in cycling animals. However, in anestrus cows the GPG treatment induced a much lower pregnancy rate (14.9%) after TAI. The replacement of the second dose of GnRH by EB (GPE-L) resulted in a pregnancy rate (43.3%) comparable to that obtained after GnRH treatment (GPG-L, 47.7%, Experiment 2). Furthermore, the use of 1/2 dose of PGF2 alpha (12.5 mg ivms, Experiment 4) resulted in pregnancy rate (43.5%) similar to that observed with the full dose (im). Both protocols GPG and GPE were effective in synchronizing ovulation in cycling Nelore cows and allowed approximately a 45% pregnancy rate after TAI. Additionally, the GPE treatment is a promising alternative to the use of GPG in timed Al of beef cattle, due to the low cost of EB when compared to GnRH agonists. (C) 2001 by Elsevier B.V.
Keywords: GnRH; estradiol; pregnancy; prostaglandin; beef cattle